“I can't imagine a radically reformed political economy that isn't built on a radically reformed public sphere.” An interview with Dan Hind - Sašo Slaček Brlek; Dan Hind (tripleC: Communication, Capitalism & Critique)
Interview with Dan Hind, advocate for media reform. We discuss the need to democratise journalism, his proposal to achieve this goal by giving the public direct control over the allocation of public subsidies in the form of public commissioning, possible objections and hurdles in the way of implementing it and his views on the pilot project of public commissioning by the Croatian Ministry of Culture.